Characteristics of Void Fraction Using Image Processing of Two-Phase Flow of Air-Pure Water and Glycerin (40-70%) on A Transparent Mini Pipe with Slope of 45o to the Horizontal - Sukamta, Sukamta; Noviyanto, Noviyanto; Sudarja, Sudarja; Sundari, Sri (Journal of Advanced Research in Experimental Fluid Mechanics and Heat Transfer, 2020)
The two-phase flow is the simplest part of multiphase flow because it only involves two components or phases that flow in a channel (either large, medium, small, mini or micro) at one particular time simultaneously, for example, liquid-gas, liquid-solid, gas-solid. The phenomenon of two-phase flow in mini channels is often found in supercomputer equipment,X-rays, heat exchangers in aerospace systems, cryogenic cooling systems in satellites, and others. Therefore, it is very necessary to study the problem there. One important problem is the void fraction characteristic caused by superficial velocity, fluid viscosity and slope. The purpose of this study was to determine the characteristics of the void fraction values on bubbly, plug, slug-annular, annular, churn, and also velocity, length and frequency patterns of bubbly and plug patterns in two-phase flow with a slope of 45 ° in horizontal capillary pipes. The study was conducted on a mini pipe with a diameter of 1.6 mm and a length of 130 mm which was installed at an angle of 45 ° to the horizontal position. The fluid used is a mixture of air-pure water and glycerin with concentrations of 40, 50, 60, and 70%. It was capturing the flow pattern video using a Nikon J4 camera with a speed of 1200 Fps, gas speed (JG) at intervals of0.025 -66.3 m / s and fluid velocity (JL) at intervals of 0.033 -4.935 m / s. To determine the value of a void fraction, a digital image processing method is used with the MATLAB R2014a and Microsoft Excel application program. This paper's new finding is that the value of the void fraction for bubbly flow indicates conditions that are not so stable and have a low value.Meanwhile, the value of the void fraction for plug flow tends to be close to 1 in a certain period; this is induced by the air cavity, which almost fills the vessel, as shown by the results of the image processing and the void time series graphs. In the churn flow pattern, the void fraction has a value that fluctuates with a moderate value.